Case Report: Catheter-based mechanical thrombectomy using the Indigo aspiration system in a case of systemic-to-pulmonary shunt thrombosis - Soszyn, Natalie; Morgan, Gareth J.; Kim, John S.; Zablah, Jenny E. (Frontiers in Pediatrics, 2023)
A 53 day old girl with absent right atrio-ventricular (AV) connection, malposed great vessels and pulmonary atresia underwent placement of a central shunt at 6 days of life. Her post-operative course was complicated by progressive desaturation and computed tomographic angiography (CTA) demonstrated near complete occlusion of her left pulmonary artery (LPA). Angiography demonstrated non-occlusive thrombus in the distal central shunt and thrombus with complete occlusion of the LPA. The IndigoTM aspiration system (Penumbra) was used to remove thrombus from the central shunt and LPA allowing placement of a stent in the narrowed LPA. Subsequent angiography showed a widely patient central shunt and LPA. The IndigoTM aspiration system (Penumbra) provides a viable option for removal of thrombus in patient’s refractory to other methods.